Unilateral Usual Ductal Hyperplasia in A 22 Years Old Male Patient: A Case Report - Setiawan, Kelvin; Rosadi, Bramastha Aires; Lawanto, Terry Renata; Rustamadji, Primariadewi (JBN (Jurnal Bedah Nasional); Vol 3 No 2 (2019): JBN (Jurnal Bedah Nasional)DO - 10.24843/JBN.2019.v03.i02.p03, 2019)
Keywords: Usual Ductal Hyperplasia, Male Breast Tumor, Breast Conserving Surgery, Triple Test Evaluation.